Dark paradise : Pacific Islands in the nineteenth-century British imagination - Fuller, Jenn (Edinburgh critical studies in Victorian culture., 2016)
Examines the way in which the British transformed the Pacific islands during the nineteenth century. The discovery of the Pacific islands amplified the qualities of mystery and exoticism already associated with 'foreign' islands. Their 'savage' peoples, their isolation, and their sheer beauty fascinated British visitors across the long nineteenth century. Dark Paradise argues that while the British originally believed the islands to be commercial paradises or perfect sites for missionary endeavours, as the century progressed, their optimistic vision transformed to portray darker realities. As a result, these islands act as a 'breaking point' for British theories of imperialism, colonialism, and identity. The book traces the changing British attitudes towards imperial settlement as the early view of 'island as paradise' gives way to a fear of the hostile islanders and examines how this revelation undermined a key tenant of British imperialism - that they were the 'superior' or 'civilized' islanders. Key Features. The first monograph to trace the Pacific islands as represented through the lens of British fiction and non-fiction across the long nineteenth century Examines texts written by Pacific islanders and published in the British press Significantly broadens our understanding of the British Pacific by analysing understudied Pacific texts and authors alongside more canonical works